Pengaruh Kepemilikan Institusional, Komite Audit, Profitabilitas, dan Kinerja Lingkungan terhadap Environmental Disclosure (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Zullaekha, Ridha Nur; Susanto, Barkah (Universitas Muhammadiyah Magelang, 2021)
This study aims to examine the factors that influence environmental disclosure, including institutional ownership, audit committee, profitability, and environmental performance. The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange from 2015-2019. The sample selection technique used purposive sampling technique. Samples were selected as many as 17 companies through the specified criteria. Hypothesis testing in this study was carried out usingmultiple linear regression analysis. The results of this study indicate that the variables of profitability and environmental performance have a positive effect on environmental disclosure. Institutional ownership variable has a negative effect on environmental disclosure. Audit committee variable has no effect on environmental disclosure.